Multidrug resistant bacteria inactivation by photodynamic therapy - Almeida, Joana Raquel Santos Leite (2011)
The development of antimicrobials promoted the idea that diseases provoked by microorganisms would diminish and would be reduced to the insignificancy to human health. However, the great amount of antibiotics used in human medicine and veterinary lead to a selection of pathogenic bacteria resistant to multiple antibiotics, being hospital wastewaters one of the most important sources of antibiotic-resistant organisms and antibiotic-resistance genes that are released into the environment. The significant increase in the development of multiple resistance mechanisms to antibiotics caused an increase in the research of alternative treatments that may be cost effective and human friendly. Antimicrobial photodynamic therapy (aPDT) is a quickly expanding technology for the treatment of diseases since it inactivates efficiently microorganisms, is cost effective and human safe. The general objective of this work was to assess the inactivation of 4 clinical multidrug-resistant bacteria by aPDT, using a tetracationic porphyrin (PS). The efficacy of aPDT was assessed in phosphate buffered saline (PBS) and in hospital residual water for each isolated bacterium and for the bacteria mixtured all together. The synergistic effect of aPDT and antibiotics (ampicillin and chloramphenicol) was also evaluated as well as the effect of sodium dodecylsulphate (SDS) on aPDT efficiency. The results show an efficient inactivation of multidrug-resistant bacteria in PBS using 5 μM of PS during 270 minutes in the presence of a light fluence rate of 40 W.m-2 (reduction of 6 to 8 log). In the residual water, the inactivation of the 4 bacteria was also efficient and the decrease in bacterial number starts even sooner. It was observed a faster decrease in bacterial number when aPDT was combined with the addition of ampicillin and chloramphenicol at concentrations of 16 and 32 μg mL-1 (MIC dose 32 μg mL-1 for both antibiotics). The efficiency of aPDT with a lower porphyrin concentration (2.5 μM) in the presence of antibiotics at MIC dose was not significantly different of that obtained when just the PS was used. The addition of SDS did not affect the efficiency of aPDT. The results of this study showed that aPDT inactivate efficiently multidrug-resistant bacteria, in hospital residual water the bacterial inactivation is faster than in PBS, the combination of antibiotics and aPDT acts more efficiently than the aPDT alone, but aPDT in the presence of SDS does not affect the efficiency of bacterial inactivation. In conclusion, aPDT is effective to combating microbial diseases transmitted by multidrug-resistant bacteria and can be used to increase the efficacy of classical antibiotics.